(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study evaluated the sustainable livelihood of shea butter utilization by the rural women of Afijio LGA, Ilora, Oyo State, Nigeria. Ilora was purposively selected because of the prominence of the market in the area. Simple random sampling was used to select 84 respondents, and structured questionnaires were administered. Descriptive statistics, regression analysis, and Likert scale ratings were used to analyze the data collected. Results revealed that most (84%) of the shea butter producers were female, while 16% were male. The modal age class of the respondents is 46-55 years, and most (42.2%) had secondary education. Regarding trading of other commodities, 32.2% of the rural women were involved in other businesses, while farming accounted for only 11.5%. Most (64.7%) respondents had 5 to 10 years of experience in shea butter production, which showed that most are experienced. Shea butter has helped provide 26.4% of rural women’s basic needs and to pay bills 18.4%. Likert scale revealed that even though rural men participate in shea butter production, they have more impact on transportation (100%) and financial support (53.4%). Shea butter has varying medicinal and economic uses, including sunburn and burn treatment, arthritis, scalp irritation, dandruff, and hair growth. It is also a good cooking oil and is the most effective use of shea butter. Age and sex, at a 1% significance level, influenced the quality of shea butter produced. The annual rate of return on shea butter production was estimated at 81%, indicating shea butter is profitable.